Leukotriene A4 Hydrolase in Rat and Human Esophageal Adenocarcinomas and Inhibitory Effects of Bestatin - Xiaopan Chen; Ning Li; Shizhi Wang; Nan Wu; Jun‐Yan Hong; X. Jiao; Mark J. Krasna; David G. Beer; Chul‐Su Yang (2003)
Background: Esophageal adenocarcinoma (EAC) is increasing at the most rapid rate of any cancer in the United States. An esophagogastroduodenal anastomosis (EGDA) surgical model in rats mimics human gastroesophageal reflux and results in EAC. Leukotriene A4 hydrolase (LTA4H), a protein overexpressed in EAC in this model, is a rate-limiting enzyme in the biosynthesis of leukotriene B4 (LTB4), a potent inflammatory mediator. We used this model and human EAC and non-tumor tissues to elucidate the expression pattern of LTA4H and to evaluate it as a target for chemoprevention. Methods: LTA4H expression was examined by western blotting and immunohistochemistry. The functional role of LTA4H in carcinogenesis was investigated by use of an LTA4H inhibitor, bestatin, in the rat EGDA model. All statistical tests were two-sided. Results: LTA4H was overexpressed in all 10 rat EACs examined, compared with its level in normal rat tissue; it was also overexpressed in four of six human EAC tumor samples, compared with its level in adjacent non-tumor tissue. In tissue sections from 20 EGDA rats and 92 patients (86 with EAC, one with dysplasia, and five with columnar-lined esophagus), LTA4H was expressed in infiltrating inflammatory cells and overexpressed in the columnar cells of preinvasive lesions and cancers, especially in well-differentiated EACs, as compared with the basal cells of the normal esophageal squamous epithelium. Bestatin statistically significantly inhibited LTB4 biosynthesis in the esophageal tissues of EGDA rats (without bestatin = 8.28 ng/mg of protein; with bestatin = 4.68 ng/mg of protein; difference = 3.60, 95% CI = 1.59 to 5.61; P = .002) and reduced the incidence of EAC in the EGDA rats from 57.7% (15 of 26 rats) to 26.1% (6 of 23 rats) (difference = 31.6%, 95% CI = 0.3% to 56.2%; P = .042). Conclusion: LTA4H overexpression appears to be an early event in esophageal adenocarcinogenesis and is a potential target for the chemoprevention of EAC.